Jean-Martin Charcot (1825–1893) and his second thoughts about hysteria - Francesco Brigo (Arquivos de Neuro-Psiquiatria)
ABSTRACT Jean-Martin Charcot's (1825–1893) concepts of hysteria evolved significantly over the last 20 years of his career. In the “Leçons du Mardi à la Salpêtrière” (Tuesday lessons), his original conception of a “dynamic lesion” coexists alongside a new psychological conception, sometimes in a rather contradictory way. According to the hand-written transcript of his Tuesday lesson on February 21st, 1888, Charcot stated: “Hysteria must be taken for what it is: psychic disease par excellence”. However, in the printed edition of the Tuesday lessons, this emphasis on psychological factors was very much softened. The different wording and corresponding shift in meaning implicitly retrieved Charcot's former conception of a “dynamic lesion”. Charcot himself had probably been made aware of the different wording by the editors, and had agreed upon it. After several years of studying this condition, Charcot was probably not confident enough in making too assertive conclusions on the psychological mechanisms underlying hysteria.